Quantitative Raman spectroelectrochemistry using silver screen-printed electrodes. (20th February 2018) - Martín-Yerga, Daniel; Pérez-Junquera, Alejandro; González-García, María Begoña; Perales-Rondon, Juan V.; Heras, Aranzazu; Colina, Alvaro; Hernández-Santos, David; Fanjul-Bolado, Pablo
Abstract: Surface enhanced Raman scattering (SERS) is a powerful technique based on the intensification of the Raman signal because of the interaction of a molecule with a nanostructured metal surface. Electrochemically roughened silver has been widely used as SERS substrate in the qualitative detection of analytes at the ultra-trace level. However, its potential for quantitative analysis has not been widely exploited yet. In this work, the combination of time-resolved Raman spectroelectrochemistry with silver screen-printed electrodes (SPE) is proposed as a novel methodology for the preparation of SERS substrates. The in situ activation of a SERS substrate is performed simultaneously with the analytical detection of a probe molecule, controlling the process related to the preparation of the substrate and performing the analytical measurement in real time. The results show the good performance of silver SPE as electrochemically-induced surface-enhanced Raman scattering substrates. Raman spectra were recorded at fairly low integration times (250 ms), obtaining useful spectroelectrochemical information of the processes occurring at the SPE surface with excellent time-resolution. By recording the microscopic surface images at different times during the experiment, we correlated the different data obtained: structural, optical and electrochemical. Finally, the in situ activation process was used to obtain a suitable in situ SERS signal for ferricyanide and tris(bipyridine)ruthenium (II) quantification. The detection of the analytes at concentrations of a few tens of nM was possible with a low integration time (2 s) and good precision, demonstrating the exceptional performance of the Raman spectroelectrochemical method and the possibility to use cost-effective screen-printed electrodes for applications where a high sensitivity is needed.